An Anatomical-Computerized Tomography (CT Scan) Study on the Arteriovenous Malformations (AVMs) in the brain of Iraqi Patients - George, Nameer T. (Journal of the Faculty of Medicine Baghdad, 2007)
Summary Background Arteriovenous malformations (AVMs) of the brain are anomalies affecting different age groups of the population, and predisposing patients to significant neurological disability from stroke, epilepsy, or other clinical manifestations. Noninvasive modalities are revealing these lesions more frequently, and with more accuracy. Previous studies on Iraqi subjects with intracranial AVMs are scarce. Objectives The aim of the study is to correlate the CT findings of intracranial ATMs with the clinical presentations, anatomic locations, the size, and the predictable origin of the arteries feeding these lesions and their venous drainage. Patients and Methods The charts and CT scans offifty-four Iraqi patients with an AIM, 31 males and 23 females (male to female ratio 1.3: 1), ranging in age from 6-74 years (mean 37.7) who were seen at the Neurosurgical Hospital-Baghdad from October 1998 to August 2002 were reviewed. Results Supratentorial AVMs were present in 53 patients; one patient had a left cerebellar AIM. The lesion was solitary, and directly localized in a single lobe, with more in the right lobes (mainly the parietal and temporal) in the non-haemorrhagic lesions, and in the left lobes of the AVMs presented with haemorrhage. The diameter of the lesion varied from less than 2.5 cm to >6.5 cm. Conchision AIM may present symptomatically at any age .The arterial and venous components of the AIM could be explained by the site of the lesion. The size of the AIM could be evaluated as a potential factor predicting future AIM haemorrhage risk. Long-term follow-up evaluation is necessary for assessing the natural history and prognosis for such lesions.